(untitled) (Global Journal of Human-Social Science, 2017)
Ensuring the availability of modern contraceptive methods both by type and quantity is crucial in the provision of quality primary health care and designing appropriate intervention strategies toward reducing maternal and child mortality This endeavor therefore is designed to make family planning commodities requirement projection based on various assumptions with the target of achieving replacement level fertility by 2020 and also estimate costs of family planning commodities Baseline data were obtained from 2007 census reports 2011 EDHS and model data for Ethiopian context The SPECTRUM by using FamPlan model was used to project these outcomes with analysis restricted to the time period 2011 2020 Spectrum and MS Excel were used to analyze and producing report for this study The projection result of the study showed that the 2011 CPR of 29 will therefore need to increase to 71 to attain the replacement-level fertility of 2 by 2020 In order to reduce fertility rate users of contraceptives should also increase accordingly